Is there a difference between disease-free survival of oral squamous cell carcinoma referred by dentists versus other physicians? -A systematic review - Ghauri, Kanza; Siddiqui, Humayun Kaleem; Khan, Farhan Raza (Journal of the Pakistan Medical Association, 2023)
Objectives: To compare disease-free survival rates in oral squamous cell carcinoma patients initially attended to and referred by dentists versus other physicians. Methods: The systematic review was conducted after registration with the International prospective register of systematic reviews at the University of York, the United Kingdom, and comprised search on Medline, PubMed, Cochrane and CINAHAL Plus databases for studies published up to December 2021. The Population-Intervention-Comparison-Outcomes-Study criteria was used to search for studies involving patients diagnosed with oral squamous cell carcinoma receiving referrals by dentist or by other healthcare providers. Disease-free survival of patients was taken as the main outcome. Customized data collection proforma was used to record data in line with the Preferred Reporting Items in Systematic Reviews and Meta-Analysis guidelines. Data was subjected to systematic, qualitative review. Results: Of the 344 studies found, 8(2.3%) were analysed in detail. Patients referred by dentists ranged from 22.6% to 54%. Males comprised 53% to 70.3% of the sample. The highest number of referrals was made by primary physicians, ranging from 27.4% to 71.6%. Upto 67.6% cases were diagnosed with stage 1 and 2 oral cancer. The highest 5-year survival rate was 75% in a study where 59% patients were diagnosed at an early stage of disease. Conclusion: The relative scarcity of studies makes it impossible to draw an association between oral cancer survival rate and type of referral. Key Words: Oral squamous cell carcinoma, Cancer-free survival, Early detection, Referrals.